2023
DOI: 10.1039/d2ew00978a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable sulphur doping in CuFe2O4 for the efficient removal of arsenic through arsenomolybdate complex adsorption: kinetics, isothermal and mechanistic studies

Abstract: Arsenic is regarded as a highly toxic element naturally exists in the ground drinking water. Due to its inherent carcinogenic nature, arsenic free water becomes necessary for healthy life. To...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Common ways to remove the dyes from water are through adsorption and coagulation [3]. However, these methods produce secondary pollutants because dyes are only changed from liquid to solid phase during the adsorption and coagulation [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common ways to remove the dyes from water are through adsorption and coagulation [3]. However, these methods produce secondary pollutants because dyes are only changed from liquid to solid phase during the adsorption and coagulation [4].…”
Section: Introductionmentioning
confidence: 99%
“…2 Common ways to remove the dyes from water are through adsorption and coagulation. 3 However, these methods produce secondary pollutants because dyes are only changed from the liquid to the solid phase during adsorption and coagulation. 4 To resolve this issue, an environment-friendly and cost-effective approach is urgently required that can utilize visible light for the removal of organic dyes from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks originated at 1635.51 and 3410.39 cm −1 and belonged to the stretching vibrations of the O-H group. 52,53 These peaks confirmed that g-C 3 N 4 and TiO 2 heterostructures could have an interfacial connection. The blocky irregular structure and presence of holes in g-C 3 N 4 allowed an active photocatalytic reaction for hydrogen production.…”
Section: Crystallinity and Structural Evaluationmentioning
confidence: 70%
“…In this work it has found that, at high and low pH, hydrogen evolution rate was decreased. Because of highly acidic and basic reaction medium, the stability of photocatalysts was affected and reduced 61 . As a result, activity of photocatalysts for hydrogen production was found to be retarded.…”
Section: Recyclabilitymentioning
confidence: 99%